The Strategy of Tuan Guru in the Election of the West Lombok Legislative - Solihan, Solihan; Hafis Bin Amat Simin, Mohamad; Sukri, Muhammad (Jurnal Review Politik, 2022)
The purpose of this research is to describe the strategy of Tuan Guru in the election of the West Lombok legislature. The research question is: What are the factors behind Tuan Guru’s entry into the world of practical politics? What is the Tuan Guru strategy in politics? What was the significant impact on the development of West Lombok in the Tuan Guru era following politics? This research uses qualitative methods based on phenomena. The finding in this research is the purpose of Tuan Guru’s involvement in politics are power and sources of power, positional power, and personal power. As for the strategy of Tuan Guru to garner support as a candidate for the legislature or executive, it is utilizing a network of students and alumni, a family network, fellow Tuan Guru, majlis ta'lim to conduct political socialization. And the last, the significant impact on the development of West Lombok in the Tuan Guru era following politics, bringing economic growth, politics, and democracy.